Falling from the Past. Geographies of exceptionalism in two novels by Jay McInerney (Altre Modernità, 2011)
Celebrating the glamorous 1980s, Jay McInerney has described the fall of the ambitions and delusions of yuppies in New York City. The vibrant atmosphere of his debut novel (Bright Lights, Big City, 1984) comes to a sudden end in Brightness Falls (1987), where the 1987 stock market crash is prophesied and narrated in its consequences on the lives of a young, brilliant couple, Corrine and Russell Calloway. Almost twenty years later, in The Good Life (2006), McInerney takes up Russell’s and Corrine’s stories again, now in the aftermath of September 11. This article focuses on the symbolic economy of the US territory. The 1980s, as they have been represented in Brightness Falls, witnessed the boisterous celebration of New York City and its centrality in the imaginary geography of the USA. When New York apparently starts crumbling under the terrorist attacks, the protagonists of The Good Life ideally (and sometimes physically) go back to their native places. In particular, one of the novel’s central characters, Luke McGavock, who starts an affair with Corrine while they are both volunteering at Ground Zero, returns to his native Tennessee, where is confronted with the memory of the Civil War. From this moment on, the novel starts tracing an implicit and highly thought-provoking parallel between the defeated nineteenth-century South and the synecdochic New York City at the turn of the twenty-first century, whose crash has engendered the dramatic need for the US to face the burden of its own history.